1
$\begingroup$

Consider the equation $$f(kx-f(x))=x=kf(x)-f(f(x))$$ for montonic $f$.

What can we say about the solutions to this equation. Comparing with Cauchy equation $f(x+y)=f(x)+f(y)$, I think the solution must be somewhat close to being linear. Any hints. Thanks beforehand.

$\endgroup$
  • $\begingroup$ The $ = x = $ in between, is that meant to be there? $\endgroup$ – Rutger Moody Jan 31 '17 at 21:36
  • $\begingroup$ @RutgerMoody yes, that is meant to be there. I think that makes the function bijective. $\endgroup$ – vidyarthi Feb 3 '17 at 11:18
2
$\begingroup$

$f(kx-f(x))=x \tag{1} $
$kf(x)-f(f(x)) =x \tag{2}$

From $(1) \implies $ $f(x) $ is surjective.


$(2) \implies $ Let $f(a)=f(b)\implies a=kf(a)-f(f(a))=kf(b)-f(f(b)) = b \implies $

$f(x)$ is injective.

This means $f(x)$ is bijective. So $f^{-1}(x)$ exists.


$(1)\implies f(kf^{-1}(x)-f(f^{-1}(x)))=f^{-1}(x) \implies f^{-1}(f(kf^{-1}(x)-x))=f^{-1}(f^{-1}(x)) \implies x =kf^{-1}(x) -f^{-1}(f^{-1}(x)) $
$(2) \implies kx-f^{-1}(x) = f(x) \implies f^{-1}( kx-f^{-1}(x)) = x $ $\implies$

If $f(x)$ is a solution to $(1)$ and $(2)$ then so is $f^{-1}(x)=kx-f(x)$



Let : $ g(x)=-f(-x) $.
$(1)\implies -f(-kx-f(-x))=x \implies g(kx+f(-x))=x \implies g(kx-g(x))=x $
$(2)\implies -kf(-x)+f(f(-x)) =x \implies kg(x)+f(-g(x))=x\implies kg(x)-g(g(x))=x $

$\implies $ If $f(x)$ is a solution to $(1)$ and $(2)$ then so is $ g(x):=-f(-x)$.


Fixed points :
From $ (2) $ we see that if there exists an $ a $ for which $f(a)=a $ then: $ kf(a)-f(f(a)) =a \implies ka =2a \implies a=0 \lor k=2 $
$f(ka-f(a))=a \implies ka-f(a) =a \implies ka =2a \implies a=0 \lor k=2 $

Also we see that if there exists an $ a $ for which $f(a)=-a $ then: $ kf(a)-f(f(a)) =a \implies -ka =2a \implies a=0 \lor k=-2 $
$f(ka-f(a))=a \implies -ka-a =a \implies -ka =2a \implies a=0 \lor k=-2 $

From the above we see that when $k=2$ , then $f(x)=x$ is a solution. And when $k=-2$ , then $f(x)=-x$ is a solution.



General solution :

(Note: I screwed up a couple of times before here. Apologies to everyone who read it, if anyone did..I do think this must be the correct argument.)

We transform $f(x)$ into a new function $g(x)$ like this : $g(x)+\frac{kx}{2}=f(x)$
Which gives :
$ g(\frac{kx}{2}-g(x))-\frac{kg(x)}{2} =(1-\frac{k^2}{4})x \tag{1a}$
$-g(\frac{kx}{2}+g(x))+\frac{kg(x)}{2} =(1-\frac{k^2}{4})x \tag{2a}$
There are two cases to consider :

Case 1 when $k^2 \neq 4 $ :

Let $g(a)=0 \implies (1a) \implies g(\frac{ka}{2}) =(1-\frac{k^2}{4})a $
$(2a) \implies -g(\frac{ka}{2} ) =(1-\frac{k^2}{4})a $

$ \implies a=0 \implies g(0)=f(0)=0 \enspace ( k^2 \neq 4 ) $



From bijectivity and monotonicity I think we can conclude that $f(x)$ and $g(x)$ must be continuous, (and maybe even differentiable).
Here I'll assume $g(x)$ can be written as a Taylor series around $x=0$ :
We calculate the first and second derivative :

$ g'(\frac{kx}{2}-g(x))(\frac{k}{2}-g'(x))-\frac{kg'(x)}{2} =(1-\frac{k^2}{4}) $
$-g'(\frac{kx}{2}+g(x))(\frac{k}{2}+g'(x))+\frac{kg'(x)}{2} =(1-\frac{k^2}{4}) $

$ g'(0)(\frac{k}{2}-g'(0))-\frac{kg'(0)}{2} =(1-\frac{k^2}{4}) $
$-g'(0)(\frac{k}{2}+g'(0))+\frac{kg'(0)}{2} =(1-\frac{k^2}{4}) $

$ g'(0) = \pm \sqrt{\frac{k^2}{4}-1} $


$ g''(\frac{kx}{2}-g(x))(\frac{k}{2}-g'(x))^2+g'(\frac{kx}{2}-g(x))(-g''(x))-\frac{kg''(x)}{2} =0 $
$-g''(\frac{kx}{2}+g(x))(\frac{k}{2}+g'(x))^2 -g'(\frac{kx}{2}+g(x))(g''(x))+\frac{kg''(x)}{2} =0 $

$ g''(0)(\frac{k}{2}-g'(0))^2+g'(0)(-g''(0))-\frac{kg''(0)}{2} =0 $
$-g''(0)(\frac{k}{2}+g'(0))^2 -g'(0)(g''(0))+\frac{kg''(0)}{2} =0 $

$ g'(0)g''(0)( k + 1) =0 \implies g''(0)=0 \enspace \lor \enspace k=-1 $
$-g''(0)(\frac{k^2}{4}+(k+1)g'(0)+g'(0)^2 -\frac{k}{2}) =0 \implies \text{(with $k=-1$ and $g'(0)^2=\frac{k^2}{4}-1$ )} \implies -g''(0)(\frac{1}{4} +\frac{1}{4}-1 -\frac{1}{2}) =0 \implies g''(0)=0 $

$\implies g''(0) =0 $ . Also the higher derivatives in $x=0$ are $0$ (I think).


So for $k^2 \neq 4 $ we have : $g(x)=\pm \sqrt{\frac{k^2}{4}-1} \cdot x$. Or : $f(x)=( \frac{k}{2} \pm \sqrt{\frac{k^2}{4}-1} ) \cdot x $

Fill this in in the original equations to check :

$g(x)= \sqrt{\frac{k^2}{4}-1} \cdot x$
$ \sqrt{\frac{k^2}{4}-1} (\frac{k}{2}-\sqrt{\frac{k^2}{4}-1} )x-\frac{k}{2}\sqrt{\frac{k^2}{4}-1} x =(1-\frac{k^2}{4})x $
$-\sqrt{\frac{k^2}{4}-1} (\frac{k}{2}+\sqrt{\frac{k^2}{4}-1} )x+\frac{k}{2}\sqrt{\frac{k^2}{4}-1} x =(1-\frac{k^2}{4})x $

$g(x)= -\sqrt{\frac{k^2}{4}-1} \cdot x$
$ -\sqrt{\frac{k^2}{4}-1}(\frac{k}{2}+\sqrt{\frac{k^2}{4}-1} )x+\frac{k}{2}\sqrt{\frac{k^2}{4}-1} x =(1-\frac{k^2}{4})x $
$+\sqrt{\frac{k^2}{4}-1} (\frac{k}{2}-\sqrt{\frac{k^2}{4}-1} )x-\frac{k}{2}\sqrt{\frac{k^2}{4}-1} x =(1-\frac{k^2}{4})x $

$\square$

Case 2 when $k^2 = 4 $ :

$ g(\frac{kx}{2}-g(x))-\frac{kg(x)}{2} =0 \tag{1b}$
$-g(\frac{kx}{2}+g(x))+\frac{kg(x)}{2} =0 \tag{2b}$

We see that $g(x)$ must be constant (see here for example : Functions $f$ satisfying $ f\circ f(x)=2f(x)-x,\forall x\in\mathbb{R}$.) and fill in as a general solution :

For $k = 2 $ we have : $g(x)= c $. Or : $f(x)= c + x $.


For $k = -2 $ we have : $g(x)= 0 $. Or : $f(x)= - x $.

$\square$





Below some solutions to modified versions :



Below some things that can be proved about the more general version of $(1)$ and $(2)$ : equation $(3)$ :

More general case without '$=x=$' in between :

$$ f(kx-f(x))=kf(x)-f(f(x)) \tag{3} $$

$f(x)=0$ and $f(x)=kx$ and $f(x)=\frac{kx}{2}$ are all solutions to $(3)$ .

$f(x)=0$ is trivial.
Let: $f(x)=kx \implies \\ f(kx-f(x))=kf(x)-f(f(x)) \implies f(kx-kx)=k^2x-f(kx) \implies 0=0 $
Let: $f(x)=\frac{kx}{2} \implies f(kx-\frac{kx}{2})=k\frac{kx}{2}-f(\frac{kx}{2}) \implies \frac{k^2x}{2}= \frac{k^2x}{2} \enspace \square $


There are many more solutions, including the ones above for $(1)$ and $(2)$.




Below a solution to a modified version of $(1)$ and $(2)$ : equation $(4)$ and $(5)$:

Modified case with '$=\frac{k^2x}{4}=$' in between :

$f(kx-f(x))=\frac{k^2x}{4} \tag{4} $
$kf(x)-f(f(x)) =\frac{k^2x}{4} \tag{5}$

$f(x)=\frac{kx}{2}$ is a solution to $(4)$ and $(5)$.


Let: $f(x)=\frac{kx}{2} \implies f(kx-\frac{kx}{2})=\frac{k^2x}{4} \implies \frac{k^2x}{4}=\frac{k^2x}{4} $ and :
$ k\frac{kx}{2}-f(\frac{kx}{2}) =\frac{k^2x}{4} \implies \frac{k^2x}{2}- \frac{k^2x}{4} =\frac{k^2x}{4} $ $ \enspace \square $

$\endgroup$
  • 1
    $\begingroup$ great answer, the answer would be complete if you provide proofs for expanding into taylor series $\endgroup$ – vidyarthi Feb 16 '17 at 11:09
  • $\begingroup$ @vidyarthi Thanks! I realize this was an assumption, it might be that this can be proved. But then again it might be that there are other exotic functions (eg fractal-like) so weird in their definition that they are non-differentiable solutions to the above. Allways hard to prove a negative. I'll get back to it if I can find an answer. $\endgroup$ – Rutger Moody Feb 16 '17 at 12:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.